Lack of protected areas and future habitat loss threaten the Hyacinth Macaw (Anodorhynchus hyacinthinus) and its main food and nesting resources - Oliveira, Maxwell da R.; Szabo, Judit K.; Júnior, Antônio dos S.; Guedes, Neiva Maria R.; Tomas, Walfrido M.; Camilo, André R.; Padovane, Carlos R.; Peterson, Andrew T.; Garcia, Letícia C. (Ibis (London, England), 2021)
Habitat loss is a major reason for population declines and thus increases extinction risk, particularly for endemic or specialist species. Protected areas are an important biodiversity conservation strategy in the face of native vegetation conversion, but local and regional factors such as anthropogenic pressure can jeopardize their effectiveness. The Pantanal biome is one of the largest inland wetlands in the world. Currently, only 11% of the Pantanal is protected, 7% with full protection and 4% under sustainable use. However, 14% of the natural vegetation of the biome was lost between 2002 and 2014, negatively affecting its biodiversity. Here, we analyse how the availability of protected areas and habitat loss affects the conservation of the Hyacinth Macaw Anodorhynchus hyacinthinus, as well as the Acuri Palm Attalea phalerata and the Manduvi Tree Sterculia apetala, its two main resources for food and nesting, respectively. We modelled potential distributions to assess the spatio‐temporal patterns of habitat loss due to the conversion of native vegetation and to evaluate to what degree currently protected areas contribute to the conservation of these three species in the Pantanal. We found that, on average, 11.8% of the suitable habitat had been converted and that 10.6% of habitat predicted as suitable is currently protected. In addition, our results indicated important areas for the three species, which are of high priority for conservation and restoration. We also identified priorities for protection and restoration to maintain native vegetation, such as the creation of corridors. We believe that the high conversion rate and the low protection of suitable areas are related to the fact that these species are associated with areas that are rarely or never flooded. In the Pantanal, these areas are more prone to the conversion of native vegetation and are poorly protected given their higher economic value compared with areas with a high frequency of flooding. These facts, and the inadequate management of these areas, such as inappropriate fire regimens, threaten the persistence of these iconic species in the Pantanal.